Factors Predicting Fertility Rate in Indonesia - Yusni Maulida; Harlen Harlen; Delfi Ranta Sari; Tehubijuluw Zacharias (Muhammadiyah University Press, 2023)
The highly competitive environment of the nowadays modern world brought about survival challenges. Hence, individuals all over the globe are striving for a quality life with the fulfillment of their basic needs. Simultaneously, the population plays an important role in determining the distribution of resources and quality of life in a particular area. At the same time, the fertility rate is an important element of the world’s population. Hence, this study aims to analyze the effect of women's education, women's participation in the labor market, income, and mortality on the fertility rate in Indonesia. Multiple regression analysis methods with Error Correction Model (ECM) analysis technique were applied. Based on the result of the research conducted, women's education, participation in the labor market, income, and mortality rates together significantly affect fertility in Indonesia in the long term. However, the results were insignificant in the short term. Moreover, based on the long-term results of the data, it is suggested that in fertility control, these factors need to be included in developing nations.